Translation and validation of Malay version of the simplified diabetes knowledge test - Md Aris, Mohd Aznan; Othman, Umair; Abdul Rahim, Nur Hidayah; Pasi, Hafizah (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2018)
Type 2 diabetes mellitus is a non-communicating disease with an increasing trend in Malaysia. One of the most important aspects in the selfmanagement of diabetes mellitus is the assessment of knowledge among diabetes patients. This study aimed to translate and validate the Malay version of Modified Diabetes Knowledge Test (DKT) questionnaire.